Pengaruh Model Kulit Bumi terhadap Gelombang ScS dan ScS-ScS - Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2009)
Cherubism is a rare, benign, autosomal dominant disorder characterized by bilateral painless expansion of the mandible and maxilla. It is a giant cell-rich jaw lesion associated with mutations in the SH3BP2 gene, leading to abnormal osteoclast activation and bone remodeling. Cherubism typically presents in early childhood and follows a self-limiting course; however, it resembles other giant cell-rich and fibro-osseous lesions radiographically and histopathologically. We report a pediatric case of cherubism followed for 6 years, emphasizing the indolent nature and importance of prolonged clinical and radiographic surveillance. Owing to its similarity to other jaw lesions, an integrative diagnostic approach incorporating histopathologic examination, imaging, and biochemical evaluation is essential for accurate differentiation. As conservative management is often sufficient, surgical intervention should be limited to cases demonstrating functional or aesthetic impairment. Our case highlights the importance of early diagnosis, particularly in sporadic presentations, to facilitate appropriate follow-up and minimize unnecessary interventions.